Answer:
?
Step-by-step explanation:
??????
2^6 (or two to the sixth power) is equal to 4^3, which equals out to 64.
Answer:
Image below
Step-by-step explanation:
<em>Hey there!</em>
<em />
Well lets graph the given inequality,
y < 3x + 1
Look at the image below.
So the right graph should look like the image below.
<em>Hope this helps :)</em>
Equation of circle
(x-h)^2 + (y-k)^2 = r^2
I believe it is
(x-2)^2 + (y+2)^2 = 16
-3x + 20 > = 8
-3x > = 8 - 20
-3x > = -12
x < = -12/-3
x < = 4
( - infinity, 4] <== interval notation